Hasil Tangkapan Rajungan (Portunus Pelagicus Linnaeus, 1758) di Perairan Pancana berdasarkan Peraturan Menteri Kelautan dan Perikanan Nomor 12 Tahun 2020 - Sabir, Muhammad; Rapi, Nuraeni L; Jumrawati, Jumrawati; Wulandari, Sri Wulandari (Jurnal Riset Diwa Bahari (JRDB), 2023)
Portunus pelagicus is one type of crab that has a very high economic value. The high selling price of crab encourages an increase in fishing effort, where the pressure of increasing fishing effort can cause less catch per effort obtained. To maintain the sustainability of the availability of fisheries resources, improve community welfare, equality of cultivation technology, investment development, increase foreign exchange, and development of cultivation and crab (Portunus spp.), the Minister of Marine Affairs and Fisheries Regulation Number 12 of 2020 was issued to re-regulate the provisions for catching and/or releasing crab, therefore this study aims to determine the feasibility of catching crab (Portunus pelagicus) based on the Minister of Marine Affairs and Fisheries Regulation Number 12 of 2020. This study uses a quantitative method by measuring the frequency distribution of carapace width and crab weight which will then determine the frequency of each class by entering the width data of each crab based on the Minister of Marine Affairs and Fisheries Regulation Number 12 of 2020. The results showed that more than 90% of the crab catches followed the Minister of Marine Affairs and Fisheries Regulation Number 12 of 2020, namely carapace width size above 10 (ten) cm and weight above 60 (sixty) grams per tail. Although the catch of unfit crabs is less than 10%, it should be released back to nature to support the sustainability of crab.